Shade Delayed Flowering Phenology and Decreased Reproductive Growth of Medicago sativa L. - Qin, Fengfei; Shen, Yixin; Li, Zhihua; Qu, Hui; Feng, Jinxia; Kong, Lingna; Teri, Gele; Luan, Haoming; Cao, Zhiling (Frontiers in Plant Science, 2022)
Alfalfa (Medicago sativa L.) is an important forage in intercropping or rotation ecosystem, and shading is the principal limiting factor for its growth under the crop or forest. Agronomic studies showed that shading would systematically reduce the biomass of alfalfa. However, little is known about the reproduction of alfalfa under shading conditions. In order to study the effect of shading on the reproductive characteristics of alfalfa, two alfalfa cultivars (“Victoria” and “Eureka”) were used to study the effect of shading levels (full light, 56.4% shade, and 78.7% shade) on alfalfa flowering phenology, pollen viability, stigma receptivity, and seed quality. Results showed that shading delayed flowering phenology, shortened the flowering stage, faded the flower colors, and significantly reduced pollen viability, stigma receptivity, the number of flowers, quantity and quality of seeds. Under shading conditions, seed yield per plant was obviously positively correlated with germination potential, germination rate, pollen viability, and thousand-seed weight. The number of flower buds, pollen viability, thousand-seed weight, and germination rate had the greatest positive direct impact on seed yield per plant. Our findings suggested that delayed flowering and reducing reproduction growth were important strategies for alfalfa to cope with shading and pollen viability was the key bottleneck for the success of alfalfa reproduction under shading. However, given that alfalfa is a perennial vegetative-harvest forage, delaying flowering in a weak light environment was beneficial to maintain the high aboveground biomass of alfalfa. Therefore, this should be taken into account when breeding alfalfa cultivars suitable for intercropping. Future research should further reveal the genetic and molecular mechanism of delayed flowering regulating the accumulation and distribution of assimilates between vegetative and reproductive organs of alfalfa under shading, so as to provide a theoretical basis for breeding of shade tolerant alfalfa cultivars.